Hypertension Control and Its Correlates Among Adults Attending a Hypertension Clinic in Tanzania. Issue 3 (17th August 2015) - Maginga, John; Guerrero, Mariana; Koh, Eileen; Holm Hansen, Christian; Shedafa, Rehema; Kalokola, Fredrick; Smart, Luke R.; Peck, Robert N.
Abstract : Hypertension control rates are low in sub‐Saharan Africa. Population‐specific determinants of blood pressure (BP) control have not been adequately described. The authors measured BP and conducted interviews to determine factors associated with BP control among adults attending a hypertension clinic in Tanzania. Three hundred adults were enrolled. BP was controlled in 47.7% of patients at the study visit but only 28.3% over three consecutive visits. Demographic and socioeconomic factors were not associated with control. Obesity and higher medication cost were associated with decreased control. Their effect was mediated through adherence. Good knowledge of (odds ratio [OR], 2.5; 95% confidence interval [CI], 1.0–6.1; P =.047), attitudes towards (OR, 2.7; 95% CI, 1.0–7.1; P =.04), and practices concerning (OR, 5.4; 95% CI, 2.3–13.0; P <.001) hypertension were independently associated with increased control, even after adjusting for mediation through adherence. Good adherence had the strongest association with control (OR, 14.6; 95% CI, 5.8–37.0; P <.001). Strategies to reduce hypertension‐related morbidity and mortality in sub‐Saharan Africa should target these factors. Interventional studies of such strategies are needed.